2011
DOI: 10.1088/0029-5515/51/9/094008
|View full text |Cite
|
Sign up to set email alerts
|

Overview of JET results

Abstract: Since the last IAEA Conference JET has been in operation for one year with a programmatic focus on the qualification of ITER operating scenarios, the consolidation of ITER design choices and preparation for plasma operation with the ITER-like wall presently being installed in JET. Good progress has been achieved, including stationary ELMy H-mode operation at 4.5 MA. The high confinement hybrid scenario has been extended to high triangularity, lower ρ * and to pulse lengths comparable to the resistive time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 66 publications
(78 reference statements)
1
49
0
Order By: Relevance
“…(67) yields about 2 MN, which gives a correct order of magnitude of the sideways force measured in JET. 2,3,5,[9][10][11]13,56,57 The estimates are obtained assuming large-amplitude m ¼ n ¼ 1 magnetic perturbation, but actually without attributing it to the plasma. For the ideal plasma, Eqs.…”
Section: Estimates Of the Sideways Forcementioning
confidence: 99%
“…(67) yields about 2 MN, which gives a correct order of magnitude of the sideways force measured in JET. 2,3,5,[9][10][11]13,56,57 The estimates are obtained assuming large-amplitude m ¼ n ¼ 1 magnetic perturbation, but actually without attributing it to the plasma. For the ideal plasma, Eqs.…”
Section: Estimates Of the Sideways Forcementioning
confidence: 99%
“…Specifically, we investigate a new FAST scenario at I p ¼ 10 MA, B T ¼ 8.5 T, with a q 95 % 2.3 that would correspond to I p % 20 MA in ITER. The possibility to safely work at q 95 < 3 (q 95 % 2.6) has been shown recently at JET, 7 although with a slight degradation of the energy confinement (H 98 % 0.9). The key point is to demonstrate in FAST, for such a low-q scenario, the possibility of using passive conducting structures and active coils to stabilize and control potentially dangerous ideal and resistive MHD modes.…”
Section: Introductionmentioning
confidence: 92%
“…2. Of course, an accurate tailoring of the current rise 7 and of the plasma heating will be necessary to drive the current profile towards the most convenient (stable) situation. An internal q ¼ 1 surface may eventually appear; nevertheless, in the present study, we have considered only equilibria without a q ¼ 1 surface, in order to allow an easier analysis of external kink and tearing instabilities.…”
Section: A Equilibrium Configurationsmentioning
confidence: 99%
“…It is well known that high-temperature plasma in tokamaks is never completely stable [1]. One can observe different instabilities, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The performed computer calculations showed that the confi nement of alphas for further plasma heating can be realized under specifi c conditions in large tokamaks only [1]. To estimate effi ciency of fast ion confi nement, the simulations require analysis of multi-dimensional distribution functions for multi-species plasma and they take many computer hours.…”
Section: Introductionmentioning
confidence: 99%